THE ROLES OF WOMEN IN THE DEVELOPMENT OF LOCAL RESOURCE BASED MSMES IN SOUTH BURU REGENCY - Santi Farinah Tuankotta; Muspida; Hendri D. Hahury (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
based Micro, Small, and Medium Enterprises (MSMEs) in South Buru Regency as an archipelagic region of Indonesia. This study employed a qualitative case study approach supported by descriptive quantitative data. Data were collected through in-depth interviews and participant observation involving 25 women MSME actors in Labuang Village, Namrole District. The findings reveal that women play a dominant and strategic role not only in production activities, particularly in trade and fisheries, but also in controlling key resources such as finances, production tools, and savings. Financial control emerges as a critical factor in ensuring MSME sustainability. Notably, in the specific context of Labuang Village, patriarchal structures commonly reported as barriers to women’s access and participation do not fully apply. Instead, women demonstrate a high degree of agency in managing both enterprises and household resources. Nevertheless, persistent challenges remain, including limited access to formal financing, which leads to reliance on informal moneylenders, as well as the dual burden arising from domestic responsibilities. This study underscores that empowering women in local resource-based MSMEs is a crucial strategy for fostering inclusive and sustainable economic development in South Buru Regency. Accordingly, this study recommends the formulation of holistic, women-centered policies that encompass inclusive access to capital, managerial and digital skills training, and the strengthening of social networks to further optimize women’s strategic roles in local economic development.